Azacitidine Nanoemulsion Formulation and Characterization for the Tumor Treatment Suppressor Genes Activity in Myeloid Leukemia Cell Lines - Sharma, Atul (Asian Journal of Pharmaceutics (AJP), 2025)
The present study aimed to develop and evaluate an Azacitidine (AZA) nanoemulsion to enhance absorption and therapeutic effectiveness. AZA, a pyrimidine nucleoside analogue, interferes with DNA methylation by inhibiting DNA methyltransferase and acts as a cytidine antimetabolite incorporated predominantly into RNA. Although clinically effective as an anticancer drug, its low absorption limits its utility. Materials and Methods: Nanoemulsions were formulated using distilled water, co-surfactants (Transcutol P, plysorbate 80), AZA, and selected oils such as oleic acid. Various water-in-oil nanoemulsion systems were prepared by high-speed homogenization. The formulations were evaluated for stability, Fourier transform infrared (FTIR) compatibility, pH, thermodynamic stability, viscosity, and in vitro drug release profiles. Results and Discussion: The optimized nanoemulsion displayed favorable physicochemical characteristics, including acceptable pH, viscosity, and thermodynamic stability. FTIR analysis confirmed the absence of major drug-excipient interactions. In vitro studies showed improved drug release compared to conventional formulations. The nanoemulsion demonstrated significant inhibitory activity (85.37%), approaching that of methotrexate (89.09%), suggesting its potential cytotoxic effect. Conclusion: The developed AZA nanoemulsion exhibited enhanced release and inhibitory activity, indicating improved therapeutic potential. These findings support its possible application as a treatment strategy for myeloid leukemia cell lines, with additional studies warranted to confirm its histone deacetylase inhibitory effects.